Transitivity Process in “The Peace and The Picnic” Album By Neck Deep - Lukman Adila Rakhmatullah; Ervina CM Simatupang (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This study aims to discover the transitivity process types in The Peace and The Panic Album and to discover the dominant types of process used in The Peace and The Panic Album. This study is conducted by using qualitative descriptive method and using the content analysis approach. The data is classified as documentation since the data were written document which using the song lyric transcripts of the album. The music album was a pop-punk music album genre entitled The Peace and The Panic by Neck Deep which released in 2017. The transcripts were downloaded from https://www.azlyrics/neckdeep. The theory used in this study was the theory proposed by Martin, Matthiessen, and Painter, 1997. In analyzing the data, Gay, Mills, and Airasian, (2012) method was used to analyze the data. As a result of analysis, it was found that the types of transitivity process were available in The Peace and The Panic Album. Transitivity process types that were found in this music album were material process, mental process, relational process, behavioral process and existential process. The only process which is not available in this music album is the verbal process. There is no any clauses indicated the verbal process. Moreover, there are 52 clauses that indicated material process, 5 clauses that indicated mental process, 29 clauses that indicated relational process, 15 clauses that indicated behavioral process, 4 clauses that indicated existential process that was found in The Peace and The Panic Album. Thus, it can be assumed that the dominant types of process found in The Peace and The Panic Album was material process, the second is relational process, the third is behavioral process, the fourth is mental process, and the last is existential process.